Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnut.2021.628845
|View full text |Cite
|
Sign up to set email alerts
|

Increased Added Sugar Consumption Is Common in Parkinson's Disease

Abstract: Objectives: There is limited information about the dietary habits of patients with Parkinson's Disease (PD), or associations of diet with clinical PD features. We report on nutritional intake in an Australian PD cohort.Methods: 103 PD patients and 81 healthy controls (HCs) completed a validated, semi-quantitative food frequency questionnaire. Food and nutrient intake was quantified, with consideration of micronutrients and macronutrients (energy, protein, carbohydrate, fat, fibre, and added sugar). Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…Briefly, 56.3% of the PD participants were male with a mean age of 67.1 years (range 35–88, standard deviation [SD 12.2]), whilst two thirds of the HCs were female, with a mean age of 62.4 years (range 18–90, [SD 15.6], p = 0.001). All relevant demographic, clinical parameter and nutritional intake information has been reported previously for this cohort ( Lubomski et al, 2020a , b , 2021a , b ; Palavra et al, 2021 ) and is reproduced in Tables 1 , 2 and Supplementary Data , where relevant to this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, 56.3% of the PD participants were male with a mean age of 67.1 years (range 35–88, standard deviation [SD 12.2]), whilst two thirds of the HCs were female, with a mean age of 62.4 years (range 18–90, [SD 15.6], p = 0.001). All relevant demographic, clinical parameter and nutritional intake information has been reported previously for this cohort ( Lubomski et al, 2020a , b , 2021a , b ; Palavra et al, 2021 ) and is reproduced in Tables 1 , 2 and Supplementary Data , where relevant to this study.…”
Section: Resultsmentioning
confidence: 99%
“…Information regarding socio-demographic factors, lifestyle, clinical management and comorbidities was collected from validated surveys, as previously reported ( Lubomski et al, 2020a , b , 2021a , b , 2021c ; Palavra et al, 2021 ). A comprehensive Food Frequency Questionnaire ( Barclay et al, 2008 ), was completed by all participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient intake was supposed to regulate the generation of SCFAs and modify PD pathogenesis [22,23]. It was reported that PD patients had a high intake of dietary fiber, which is the source of SCFAs [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support increased physical activity being positively associated with cognitive function and a reduced likelihood of having MCI or PDD. Encouragement of PD patients to remain socially active, seek help if feeling depressed or anxious, adopt depression coping strategies, maintain physical exercise, eat a healthy diet and engage in cognitive training interventions have been proposed as a multidisciplinary approach to optimising NMS and cognitive impairment in PD (36,(56)(57)(58)(59). These interventions would be more beneficial at the MCI stage of disease, making early identification of these patients critical.…”
Section: Discussionmentioning
confidence: 99%